# math

posted by
**jim**
.

simplify 12b^-6/3a^0

you should read my notes on "rob"'s questions if you're not the same person. lol

if that's 12(b^-6), then the answer is 12/(b^6)

if that's (12b)^-6, then the answer is 1/((12^6)*(b^6))

12b^-6/3a^0. I think this is

12(b^-6)/3(a^0).

a^0 = 1; therefore,

12(b^-6)/(3*1).

Move b^-6 to the denominator.

12/[3*(b^6)].

Divide 12/3 = 4

4/(b^6)

p.s. i'm reading the question as (12b^-6)/(3a^0)

It doesn't matter.

(12b^-6)/(3a^0) =

(12*b^-6)/(3*a^0)=

(12*b^-6)/(3*1)=

12/[3*1*(b^6)]=

4/(b^6). For example,

3a^0 = 3*a^0 = 3*1 = 3 AND

(3a^0) = (3*a^0) = (3*1) = 3 BUT

(3a)^0 = (3^0*a^0)=(1*1)= 1.

Similarly,

12b^-6 = 12*b^-6 = 12/b^6 AND

(12b^-6)=(12*b^-6)=12/b^6 BUT

(12b)^-6 = 1/(12b)^6 = 1/[(12^6)*(b^6)]= 1/(2,985,984*b^6).